2009
DOI: 10.1590/s0100-84042009000200012
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia e histoquímica das estruturas secretoras da folha de Casearia decandra Jacq. (Salicaceae)

Abstract: -(Anatomy and histochemistry of secretory structures from the leaf of Casearia decandra Jacq. (Salicaceae)). Extensive investigations have emphasized the therapeutic properties of Casearia species related with compounds secreted by specialized structures in the leaves. Therefore, the objective of this study was to characterize anatomical and histochemically the secretory structures present in leaves of C. decandra. Material was collected from natural populations of Mata da Biologia (Zona da Mata of Minas Gerai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
1
0
6
Order By: Relevance
“…E. uniflora presents ducts and secretory cavities in its mesophyll (Amstrong et al 2012, Retamales & Scharaschkin 2015, Pacheco-Silva & Donato 2016, where oil resins and terpene compounds are synthesized (Thadeo et al 2009, Stesevic et al 2016, Bomboa et al 2017). The plant's essential oil, composed primarily of terpenes, is utilized by pharmaceutical and cosmetics industries because of its antioxidant activity (Victoria et al 2012), which can be used against human tumor cells, as demonstrated by Ogunwande et al (2005), while working with Leishmania amazonensis (Rodrigues et al 2013, Silva et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…E. uniflora presents ducts and secretory cavities in its mesophyll (Amstrong et al 2012, Retamales & Scharaschkin 2015, Pacheco-Silva & Donato 2016, where oil resins and terpene compounds are synthesized (Thadeo et al 2009, Stesevic et al 2016, Bomboa et al 2017). The plant's essential oil, composed primarily of terpenes, is utilized by pharmaceutical and cosmetics industries because of its antioxidant activity (Victoria et al 2012), which can be used against human tumor cells, as demonstrated by Ogunwande et al (2005), while working with Leishmania amazonensis (Rodrigues et al 2013, Silva et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Substâncias como compostos fenólicos promovem efeito adstringente, por exemplo, os taninos são conhecidos por sua ação antipatogênica (Thadeo et al 2009).…”
Section: Raizunclassified
“…Estruturas secretoras são encontradas em diversas famílias vegetais (Angiospermas e Gimnospermas) [1] . São utilizadas como caráter taxonômico devido a posição que ocupam nas espécies e variedades em que ocorrem, além disso apresentam variação conforme a sua morfologia, anatomia e natureza da secreção [2][3][4][5][6][7][8][9][10][11][12] .…”
Section: Introductionunclassified